Integrative Model of Green Human Resource Management Based on Islamic Values in Realizing Sustainable Islamic Education - Diantoro, Fery (IAIN PONOROGO, 2025)
This study aims to construct an integrative model of Green Human Resource Management (GHRM) grounded in Islamic spirituality within the context of sustainable Islamic education institutions. Employing a qualitative library research approach, the study systematically reviewed eight reputable international journal articles and relevant classical Islamic literature. The data were analyzed using content analysis and integration mapping to explore the relationship between green human resource management dimensions (green leadership, recruitment, training, knowledge sharing, and creativity) and Islamic spiritual values such as amanah (trust), ihsan (excellence), ta'awun (collaboration), ' ilm (knowledge), and tajdid (renewal). The findings reveal the development of an Islamic green human resource management Ecosystem, a conceptual model oriented toward Maslahah al-'Ammah (universal benefit) through three pillars of sustainability: environmental, social, and spiritual. This model extends Social Exchange Theory and the Resource-Based View by incorporating a dimension of faith-driven sustainability. The study concludes that human resource management in Islamic education should transcend administrative efficiency by embedding spiritual ethics and the moral responsibility of humans as khalifah (stewards of the earth).